Порівняльний аналіз ефективності полікозанолу та симвастатину в корекції порушень ліпідного обміну, параметрів інсулінової резистентності у хворих на цукровий діабет 2-го типу з дисліпопротеїнемією - Сергієнко, О. О.; Сергієнко, В. О.; Гоцко, М. Є.; Урбанович, А. М.; Сегін, В. Б. (Clinical Endocrinology and Endocrine Surgery, 2013)
The aim of the study was to conduct a comparative analysis of policosanol and simvastatin monotherapy effectiveness and their combination on the dynamics of lipid metabolism, circulating insulin, insulin resistance (IR) parameters in patients with type 2 diabetes mellitus (DM) and dyslipoproteinemia (DLP). The study involved 62 patients with type 2 DM and DLP. In the blood of patients, the levels of total cholesterol (TC), triacylglycerol (TG), high density lipoprotein cholesterol (HDLC) and low density lipoprotein cholesterol (LDLC) the content of immunoreactive insulin (IRI), the indicators of IR. Found that in patients with type 2 DM and DLP been a distinct increase in circulating levels of IRI, IR indices. Policosanol at 20 mg/day shows expressive lipid-lowering effect, which manifests itself fairly significant reduction in TC concentration, HSLPNP circulating IRI correction parameters TS and increasing content HSLPVG in the first week of the 4th of appointment and maintained over a 3-month course of treatment. The effectiveness of policosanol (20 mg/day for 3 months) in the treatment of birefringence, the correction parameters of IR in patients with type 2 DM compared with the same dose of simvastatin. The use in treatment of patients with type 2 DM and DLP policosanol (20 mg / day) in combination with simvastatin (10 mg / day) for 12 weeks, contributes to a more pronounced lipid-lowering effect, the correction parameters of IR.